Multistep block method for solving Volterra integro-differential equations - Mohamed, Nurul Atikah; Abdul Majid, Zanariah (Institute for Mathematical Research, Universiti Putra Malaysia, 2016)
In this paper, we use multistep block method for solving linear and non-linear Volterra integro-differential equations (VIDEs) of the second kind. The VIDEs will be solved by using the combination of multistep block method of order three and Newton-Cotes quadrature rule of suitable order. The proposed method will solve VIDEs for K (x, s) = 1 and K (x, s) ≠ 1. The stability region of the method will be given. Numerical problems are included to represent the performance of the proposed method.